THE NEXUS BETWEEN PUBLIC EXPENDITURE AND INFLATION IN THE MEDITERRANEAN COUNTRIES - MAGAZZINO, Cosimo (Theoretical and Practical Research in Economic Fields, 2011)
The aim of this article is to assess the empirical evidence of the nexus between public expenditure and inflation for the Mediterranean countries during the period 1970-2009, using a time-series approach. After a brief introduction, a concise survey of the economic literature on this issue is shown, before discussing the data and introducing some econometric techniques. Stationarity tests reveal, generally, that public expenditure/GDP ratio is a I(1) process, while prices index is a I(2) process. Moreover, a long-run relationship between the share of public expenditure and inflation is found for Cyprus, France, Greece and Portugal. Furthermore, Granger causality tests results show a short-run evidence of a directional flow from inflation to expenditure for Cyprus, France and Spain; and of a bidirectional flow for Italy, Malta and Portugal. Some notes on the policy implications of our empirical results conclude the paper.